(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Avascular necrosis (AVN), also called osteonecrosis, aseptic necrosis, or ischemic bone necrosis, is a condition that occurs when there is loss of blood supply to the bone, an interruption to the blood supply causes bone to die. If not stopped this process eventually cause the bone to collapse. It is the most challenging condition of the present era in orthopedics. In Ayurveda it can be co-related with the Asthi Majja Gata Vata due to similar sign and symptoms of Avascular necrosis of neck of femur. Aim and objectives: To assess the efficacy of Manjisthadi Kshara Basti, Rooksha Choorna Pinda Swedana, Pizhichil and Shastikashali Pinda Swedana in the management of AVN. Objective was to stop the further deterioration of the hip joint and to reduce the chances of surgical intervention in managing AVN. Materials and methods: A diagnosed and non operated case of Avascular necrosis of stage 3 with complaints of pain of bilateral hip joint, restricted movements and limping gait approached the out-patient division of the hospital and was managed by Rooksha Choorna Pinda Swedana, Manjisthadi Kshara Basti, Pizhichil and Shastikashali Pinda Swedana. Observation and Result: Significant improvement was noticed after the treatment. Pain was reduced significantly with improvement in range of movement. Patient was able to walk and climb stairs after the treatment without pain and stiffness. There was reduction in VAS scale, marked improvement was noticed in Harris Hip Score.